Development of design guidelines for fin-and-tube heat exchangers with low-GWP refrigerants. (November 2022) - Saleem, Saad; Bradshaw, Craig R.; Bach, Christian K.
Abstract: Regulatory changes worldwide are requiring air conditioning and heat pump equipment manufacturers to switch refrigerants to alternatives with reduced global warming potential (GWP). Design of air-to-refrigerant fin-and-tube heat exchangers (FTHXs) is critical to overall performance of this equipment and is not currently well understood with low-GWP refrigerants. This paper presents a simulation study exploring the impact of design changes for a FTHX used in an indoor residential evaporator originally designed for R410A. Simulation results are used to generate design guidelines for FTHXs using HFO refrigerants R1234yf and R1234ze(E), evaluated using cooling capacity, refrigerant-side pressure drop and ratio of the two as critical metrics. When evaluated at identical operational conditions, with fixed refrigerant outlet superheat, it was found that for a fixed slab size, the FTHX was most sensitive to number of circuits, followed by tube diameter, number of tubes in the FTHX, and fin density. For the low-GWP HFOs, circuitry modifications led to maximum increase in FTHX capacity of 20%, and maximum decrease in refrigerant-side pressure drop of 88.6%. Based on simulation results, it is concluded that additional coil face area is required to match both capacity and refrigerant pressure drop, compared with R410A, this is demonstrated with two proposed FTHX designs. One design prioritizes increased FTHX capacity, and the other a reduction in refrigerant pressure drop. All these results culminated in design guidelines for HFOs that suggest it will be challenging to achieve both the same capacity and pressure drop characteristics as R410A without modifications to FTHX size.